(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article examines issues related to improving the financial support system of state higher education institutions, specifically focusing on the Tashkent state university of economics Effective financing of higher education institutions is crucial for improving education quality, promoting scientific research, and developing modern infrastructure. The paper analyzes the current state of funding, the allocation of state budget resources, and the advantages of cooperation with the private sector. The research presents proposals for introducing innovative approaches to financing, making effective use of grants and state subsidies, and attracting additional financial resources. The results can serve as a practical guide for developing strategic decisions to ensure financial sustainability and development of higher education institutions.